Bioeconomy and biofuels: the case of sugarcane ethanol in Brazil (2021)
Brazilian bioethanol is one of the most prominent biofuels produced on a large scale, representing 30% of the global fuel ethanol production share. Around 8.6 billion gallons were produced in 2019, second only to the US fuel ethanol production in the same period (15.8 billion gallons). Obtained from sugarcane in a highly energy-efficient process, the biofuel, which can be used in Brazil as 100% ethanol (hydrated, minimum mass content of 92.5%) or in a volume proportion of 27% (anhydrous ethanol) in common gasoline, has contributed to the reduction of oil dependency and CO2 emissions, as well as to the development of an important economic sector. Pioneer biofuel policies and important advances in science and technology led to the establishment of a 46% renewable energy matrix. In this manuscript, an overview of the impacts of ethanol production and utilization will be given, with respect to environmental and socio-economic concerns. The public policies and some technical aspects of sugarcane and ethanol production and energy cogeneration will be reviewed and discussed. © 2021 Society